Diversity of micro-fungi associated with aerobic composting process of organic wastes - Thi Thu Hang, Pham; Thanh Minh, Nguyen; Thi Yen Nhi, Tran; Thi Hoanh, Nguyen; Hoang Dang Khoa, Dinh (Vietnam Journal of Biotechnology, 2020)
Organic waste is gradually degraded during composting process, producing carbon dioxide, water, heat, and humus, the relatively stable end product. The degradation process is carried out by living organisms, of which fungi appear to have the most important role since they break down tough debris (cellulose, lignin, and other resistant materials), enabling other microorganisms to continue the decomposition process. In Binh Duong province, municipal organic wastes, recently, being treated by aerobic composting process at industrial scale. In order to properly control the biological composting process and maximize its efficiency, the understanding of involved microorganisms is essential. Therefore, the objective of this study was to isolate and identify the fungi associated with large scale municipal biosolid waste composting process in Vietnam. In this study, we have isolated 10 morphologically different fungal strains from the composting materials, and classified based on morphological characteristics and 18S rDNA sequences. The results showed that these fungal strains belonged to four different genera, including Aspergillus, Penicillium, Monascus, and Trichoderma. Our observation is in consistent with previous study, which found that Aspergillus, Penicillium are dominant fungi in composting materials due to their able to survive high temperatures and break down variety of bio-solid wastes. Beside of that, the two other genera Trichoderma and Monascus are widely known for their ability to break down lignin-rich materials which difficult for biodegradation. The results would be a useful reference for further studies of diversity, and functions of fungi that involved in municipal biosolid waste composting process in Vietnam environmental conditions.